Periodic waves and solitons in a nonlinear fibre with resonant impurities - Cavalcanti, S. B.; Kamchatnov, A. M.; Kraenkel, Roberto André [UNESP]; Umarov, B. A. (Taylor & Francis Ltd, 2002)
We shall consider a coupled nonlinear Schrodinger equation- Bloch system of equations describing the propagation of a single pulse through a nonlinear dispersive waveguide in the presence of resonances; this could be, for example, a doped optical fibre. By making use of the integrability of the dynamic equations, we shall apply the finite-gap integration method to obtain periodic solutions for this system. Next, we consider the problem of the formation of solitons at a sharp front pulse and, by means of the Whitham modulational theory, we derive the amplitude and velocity of the largest soliton.